2010
DOI: 10.3109/10641950903214617
|View full text |Cite
|
Sign up to set email alerts
|

Association of –2548 G/A Polymorphism in the Leptin Gene with Preeclampsia/Pregnancy-Induced Hypertension

Abstract: Preeclampsia/pregnancy induced hypertension appears to be associated with higher circulating leptin and lower SLR levels, and with the AA genotype of −2548 G/A polymorphism of the leptin gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…It is thought to arise due to abnormal placentation followed by a maternal systemic disorder. Several studies including ours have shown that PE/PIH is associated with elevated circulating leptin levels and reduced levels of soluble leptin receptor compared to normotensive pregnancies [11-14]. We previously demonstrated that a polymorphism in the leptin gene increases risk of PE/PIH [14].…”
Section: Resultsmentioning
confidence: 99%
“…It is thought to arise due to abnormal placentation followed by a maternal systemic disorder. Several studies including ours have shown that PE/PIH is associated with elevated circulating leptin levels and reduced levels of soluble leptin receptor compared to normotensive pregnancies [11-14]. We previously demonstrated that a polymorphism in the leptin gene increases risk of PE/PIH [14].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the intensive studies devoted to LEP gene expression, only some works have focused on the analysis of the hereditary variability of this gene and its role in changing the transcription level and the structure of susceptibility to pregnancy failure. It was shown that carriers of the AA genotype of the rs2167270 locus (G19A) located in the promoter region of the LEP gene have elevated levels of expression of this gene in the blood, as well as the risk of PE and hypertension [44]. Association between another polymorphism (G2548A) localized at the LEP gene promoter with gestational diabetes [45] was found in the Czech population.…”
Section: Discussionmentioning
confidence: 99%
“…These genes and proteins may be connected to atherosclerosis, diabetes, and Alzheimer's disease. In addition, Sugathadasa et al [39] showed that preeclampsia appears to be associated with the AA genotype of -2548 G/A polymorphism of the leptin gene. Genetic factors such as leptin gene polymorphism may increase the susceptibility of pregnant women to develop preeclampsia.…”
Section: Metabolic Systemmentioning
confidence: 99%